The Measure of Financial Stability and its Impact on Foreign Direct Investment: Evidence from BRIC Nations - Kalsie, Anjala; Dhamija, Jyoti; Arora, Ashima (International Journal of Accounting & Finance Review, 2020)
The stability of the economy has explicitly become a key objective for fiscal, economic, and monetary policy. It is a broader term described by different aspects of finance and the financial system. One variable cannot be recognized for defining and achieving stability. The purpose of this paper is two-fold, one to construct four measures of financial stability (MFS). The second purpose is to use the four constructed measures of financial stability in two stage least square (TSLS) regression framework to know the impact of MFA on Foreign Direct Investment (inwards) of BRIC for a period from 2000-2017. In case of Brazil, all the four measures of financial stability are significant. In case of Russia, government finances are not appropriately managed. In case of China, the large inflow of FDI is because of government policies as rest of the measures are negative. In case of India, the government measures are not efficient to attract the FDI.The openness of the economy is positively contributing to FDI in all countries except India. Of all the four nations Brazil is on the right path.JEL Classification Codes: F4, F6, H11, E60.